Hybrids, Differences, Visions: On the Study of Culture - Baraldi, Claudio (Davies Group, Publishers, 2011)
Intro -- Title page -- Copyright page -- Contents -- Contributors -- Preface -- Introduction: On the study of culture -- Part I: Culture, Philosophy, Anthropology -- Introduction -- Human Adaptation to Culture -- Historico-Cultural Anthropology -- On the phylogenesis of utensils -- Part II: Intercultural Studies -- Introduction -- Global multiculture -- Situating Cultural Studies in Communication -- Cultural research at the margins of experience -- Part III: Languages and culture -- Introduction -- Other languages, other cultures -- Ethnopragmatics and Beyond -- Cultural Studies "at the limits of truth" -- Social Styles in Multimodal Texts -- Part IV: Historiography and "culture" -- Historiography and "culture" -- Imperial culture and cultural imperialism -- "Visual Culture": Form, Genre and History in a Film by Yervant Gianikian and Angela Ricci Lucchi.
Description based upon print version of record
Keywords: Electronic books